HAKIKAT TUJUAN PENDIDIKAN AGAMA ISLAM DALAM BERBAGAI PERSPEKTIF - H. Husaini (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The essence of educational goals in various perspectives is to look further about the goals of Islamic education in general and specifically. The study of this research is to use literature, both journals and books. The results showed that the nature of the purpose of education in Islam is not limited to the goals of Islamic education but as a whole to shape human beings according to their characteristics.